The Use Emb (Engineering Mechanics Book) Mobile App To Train Students’ Digital Literacy Skills During Covid-19 Pandemic - Ravi, Ahmad; Polonia, Betti Ses Eka (Tarbiyah : Jurnal Ilmiah Kependidikan, 2021)
Learning media plays an essential role in conveying material to students. Learning media can be divided into media that Teacher directly use in learning and media made by Teacher that later adapted to the abilities and needs of students. Engineering mechanics is one of the primary subjects that civil engineering students must master at. The engineering mechanics course discusses the analysis of the balance of a structure. Students can use mobile application-based teaching materials as online learning media amid the COVID-19 pandemic. Engineering mechanics book, we called EMB, can be used by students to study independently at home during learning online but still in the monitoring/monitoring of Teacher (lecturers). The research and development use ADDIE design. The stage includes 1) Analysis, 2) Design, 3) Develop, 4) Implementation, and 5) Evaluation. EMB product had been tested the validity and implementation during the learning process. EMB got 3.32 valid results for the product. EMB can also train students in digital literacy. Students' digital literacy is in the quite proficient category. This condition is not regardless of the influence of student habits in using technology which is more often used for online communication and entertainment. The frequency of using digital technology for entertainment purposes is higher compared to use for academic purposes.